Optimal Corporate Governance and Compensation in a Dynamic World - Noe, Thomas H.; Rebello, Michael J. (Review of Financial Studies, 2012)
[We model long-run firm performance, management compensation, and corporate governance in a dynamic, nonstationary world. Many features of governance and compensation that have caused consternation among commentators arise naturally in this dynamic setting, even though boards are rational and managers are powerless. Compensation changes depend on changes in the evolution of a latent state variable outside the manager's control.Board passivity is positively correlated with both the value of management compensation and the firm's good fortune. Managerial opportunism tends to follow sudden reversals of good fortune. Moreover, managerial private benefits, by increasing managers' stake in the long-run viability of the firm, may actually ameliorate agency conflicts.]